Genetic Profiles of Escherichia coli Isolated from Indonesian Tempeh Based on Enterobacterial Repetitive Intergenic Consensus- Polymerase Chain Reaction (ERIC-PCR) - QURROTA A’YUN; ANTONIUS SUWANTO; TATI BARUS (Microbiology Indonesia, 2015)
Tempeh is a famous Indonesian fermented food derived from soybeans inoculated with Rhizopus sp. Tempeh production varies depend on the producers and often conducted in an uncontrolled condition. This condition could lead to the growth of Escherichia coli which is known as bacterial indicators of environmental hygiene. Some strains of E. coli could induce diarrhea, acute gastroenteritis or gastrointestinal tract infections. The aim of this study was to compare genetic diversity of E. coli isolates from tempeh with medical isolates employing ERIC-PCR method. In this study, 63f and 1387r primers were used to amplify 16S rRNA genes, and ERIC 1R and ERIC 2 primers were used for ERIC-PCR analysis. Tempeh samples were obtained from four producers in Bogor. Thirty-three isolates of E. coli were successfully isolated from tempeh samples produced by only two producers, we could not obtain E. coli isolates from the other two producers. In addition, the same tempeh samples could carry different genotypes of E. coli. On the other hand, the same genotypes could be found in different tempeh samples. Based on phylogenetic tree analysis, E. coli from tempeh could be separated from medical isolates. We showed that E. coli isolates derived from tempeh were genetically different from those of medical or pathogenic isolates.